Development of the self-concept during adolescence. - Sebastian, C; Burnett, S; Blakemore, S (2008)
Adolescence is a period of life in which the sense of 'self' changes profoundly. Here, we review recent behavioural and neuroimaging studies on adolescent development of the self-concept. These studies have shown that adolescence is an important developmental period for the self and its supporting neural structures. Recent neuroimaging research has demonstrated that activity in brain regions associated with self-processing, including the medial prefrontal cortex, changes between early adolescence and adulthood. These studies indicate that neurocognitive development might contribute to behavioural phenomena characteristic of adolescence, such as heightened self-consciousness and susceptibility to peer influence. We attempt to integrate this recent neurocognitive research on adolescence with findings from developmental and social psychology.